(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Islamic ideology has formed the basic path which different peoples has walked through , until Modernity showed up , which entered new principles to the Islam and Islamic communities and the most important ones of these principles were the Separation between religion and state and follow the rational consideration in the study of the teachings and legislation of Islam and subject them to constructive criticism , which changed its principles and purposes and transformed it from a holy steady thing to another modern historical thing that seeks to give people priority in existence and self-affirmation. This Modernist Renaissance has affected the Islam as much as the eastern countries . It was the result of knowing the principles and achievements of modernity which had shown up in the west through the fifteenth and sixteenth centuries , and declared the birth of the free thinker The master of himself and the lord of society , The new Man who uses his mind, knowledge and thought to solve all the problems and difficulties he faces whether natural, social, political, cultural and economic, and he gives the appropriate solutions to produce ideal forms to achieve his dream of proving himself and liberating him from all that binds him from both natural or human traditions and laws, so that man becomes the basis of knowledge and existence . But the most important question here is what is the impact of the new principles of modernity on Islamic societies ? And Will these principles contribute to the development of Islamic societies?